THEORETICAL AND METHODOLOGICAL ASPECTS OF FORMING PEDAGOGICAL ACTIVITY (TAMADDUN NURI JURNALI, 2025)
This article discusses the history of the formation of pedagogical activity and the theoretical and methodological foundations of it. The essence of pedagogy is to transfer the necessary life-related applications and experiences from the older generation to the younger generation. The concept of education in pedagogy forms mental maturity and worldview based on the knowledge gained in the growing generation. Pedagogy summarizes the experiences in the field of education and upbringing and shows the prospects for the future development of upbringing.